Immunohistochemical Studies of Age-Related Changes in Cell Proliferation and Angiogenesis during the Healing of Acetic Acid-Induced Gastric Ulcers in Rats - A. Folorunsho Ajayi; S. Babafemi Olaleye (The Scientific World Journal)
Cell proliferation and angiogenesis are of utmost importance for healing to take place. The KI67 and EGFR proteins are markers of cell proliferation, while CD31 and factor VIII are markers of angiogenesis. To elucidate the mechanism responsible for delayed healing of the gastric injury in old age, we analyzed the expression of these markers in rats of different months during the healing of an acetic acid-induced gastric ulcer. Male Wistar rats (aged 3, 6, 12, and 18 months) divided into four groups, according to their ages, formed the experimental animals. Stomach tissue samples were collected on days 3, 7, 14, and 21 after induction for assessment of ulcer healing. The area of gastric mucosa healed was inversely proportional to age. The expression of markers of proliferation (KI67 and EGFR) and angiogenesis (factor VIII and CD31) decreased significantly (p<0.05) in older rats when compared with younger ones (3 months > six months > 12 months > 18 months) on days 7, 14, and 21 after induction of gastric ulcer. This study revealed that the slower gastric ulcer healing rate in older rats might be due to reduced epithelial cell proliferation and angiogenic activities.